2012
DOI: 10.1097/mao.0b013e3182544cba
|View full text |Cite
|
Sign up to set email alerts
|

Air-Bone Gap Component of Inner-Ear Origin in Audiograms of Cochlear Implant Candidates

Abstract: In cochlear implant candidates, the presence of a third window could cause an ABG because of stapes motion-induced shunting of acoustic energy outside the cochlear duct in response to air-conducted stimuli while bone conduction is preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This study confirms previous findings that the ABG was the largest in patients with LVA at lower frequencies [13,20,21] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study confirms previous findings that the ABG was the largest in patients with LVA at lower frequencies [13,20,21] .…”
Section: Discussionsupporting
confidence: 82%
“…An examination of the literature studies revealed that the hearing loss associated with IP-II and LVA malformations is heterogeneous, and the conductive component is not associated with middle ear pathologies [2,12,13,17,18,[20][21][22][23][24][25][26] . Roesch et al [25] found that patients with IP-II and isolated LVA malformations were diagnosed not only with severe to profound hearing loss but also with moderate asymmetrical hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Participants included patients who underwent cochlear implant surgery at a tertiary university-affiliated medical center in 2000-2012. On the basis of previous findings that patients before and after cochlear implantation may have an ABG in the presence of a normal middle ear [6], and the limitation of BC measurements in severe-to-profound hearing loss, we restricted the study group to patients with a known ABG of [10 dB for at least three consecutive frequencies (250, 500, 1,000 Hz) who were able to cooperate during behavioral audiometry. Only those in whom BC thresholds could be reliably masked were included.…”
Section: Setting and Patientsmentioning
confidence: 99%
“…The study was approved by the institutional ethics committee (approval number 6184; 2012). The preoperative findings in some of the participants were presented in our earlier study [6].…”
Section: Setting and Patientsmentioning
confidence: 99%
See 1 more Smart Citation